1994
DOI: 10.2165/00003088-199426030-00004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Fluoxetine

Abstract: Fluoxetine is well absorbed after oral intake, is highly protein bound, and has a large volume of distribution. The elimination half-life of fluoxetine is about 1 to 4 days, while that of its metabolite norfluoxetine ranges from 7 to 15 days. Fluoxetine has a nonlinear pharmacokinetic profile. Therefore, the drug should be used with caution in patients with a reduced metabolic capability (i.e. hepatic dysfunction). In contrast with its effect on the pharmacokinetics of other antidepressants, age does not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
174
2
6

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(185 citation statements)
references
References 62 publications
3
174
2
6
Order By: Relevance
“…Our finding that the steady state brain SSRI concentrations were about 10 times higher than plasma concentrations is compatible with its pharmacokinetic profile, with a reported apparent distribution volume of approximately 20 in humans for fluvoxamine (Palmer and Benfield 1994;Wilde et al 1993) and 12 to 43 for fluoxetine (Altamura et al 1994), indicating considerable uptake of the drug into tissue spaces. The result that no correlation was found between the steady state brain or plasma concentrations and the daily dose indicates that there can be a considerable variability of plasmatic levels relative to treatment dose.…”
Section: Drug Localization and Distributionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our finding that the steady state brain SSRI concentrations were about 10 times higher than plasma concentrations is compatible with its pharmacokinetic profile, with a reported apparent distribution volume of approximately 20 in humans for fluvoxamine (Palmer and Benfield 1994;Wilde et al 1993) and 12 to 43 for fluoxetine (Altamura et al 1994), indicating considerable uptake of the drug into tissue spaces. The result that no correlation was found between the steady state brain or plasma concentrations and the daily dose indicates that there can be a considerable variability of plasmatic levels relative to treatment dose.…”
Section: Drug Localization and Distributionsupporting
confidence: 83%
“…In this study, plasma steady state concentrations obtained were found to be somewhat higher than the values from the literature for fluvoxamine (Palmer and Benfield 1994;De Vries et al 1993) and fluoxetine (Altamura et al 1994) studies. The discrepancies can be accounted for by the difference between single dose and long term multiple dose studies (Kelly et al 1989) for which the values are comparable.…”
Section: Subject Population and Clinical Usefulnesscontrasting
confidence: 76%
See 1 more Smart Citation
“…Given the importance of prolonged antidepressant treatment for clinical recovery from depression, association of PLCg1 with Trk was also analyzed after long-term FLX (0.08 mg/ml FLX in drinking solution, 21 days) and water administration (n ¼ 8-9/ group). In the drug treatment group, average plasma FLX levels were clinically relevant being 268733 ng/ml (Altamura et al, 1994) at the time of brain tissue dissection. This FLX administration protocol has been previously shown to produce long-term alterations in neuroplasticity and animal behavior (Santarelli et al, 2003).…”
Section: Antidepressants Increase the Activation Of Trkb Plcc1mentioning
confidence: 99%
“…Since therapeutic doses of fluoxetine result in a plasma concentration of approximately 1 AM (Altamura et al, 1994), we examined the effects of 1 AM fluoxetine on the (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%